Hong-Hui-Xiang Alleviates Pain Hypersensitivity in a Mouse Model of Monoarthritis - Wei Gao; Di Wang; Xinlu Yang; Tingting Pan; Xiaoqing Chai; Zhi Zhang (Pain Research and Management)
Background. Hong-Hui-Xiang (HHX) is a sterilized aqueous solution extracted from Illicium lanceolatum A.C. Smith widely used for pain relief in China. Despite its history, it is not well understood. In the present study, we used a mouse model of arthritic knee pain to investigate the antinociceptive effects of HHX and its potential side effects on weight and respiratory function, as well as on the liver, kidney, and heart. Methods. Mice were randomly assigned to four groups: saline and HHX at three doses (1 μl, 10 μl, and 50 μl). Each group was randomly divided to two subgroups: saline and CFA. After the first injection of HHX or saline on day 7, mechanical hyperalgesia was tested via the hind paw. Only after the tests had established that the analgesic effect had subsided was the next injection administered. A total of five injections were administered. Blood, knee joints, and other organs were collected for histopathological observation and biochemical detection. Objectives. We found that mechanical threshold of hind paw increased 2 h after of the initial injection HHX (10 μl and 50 μl), which lasted for at least 3 h. The analgesic effect lasted for three days after the second injection on day 8 and was approximately maintained for five days each time after the third injection. We also found a reduction in the diameter of the knee joint and suppression of synovial inflammation in response to treatment of HHX (10 μl and 50 μl). Meanwhile, HHX had no toxic effects on the liver, kidneys, and heart via histological and biochemical assays in all groups. Conclusion. HHX exerts antinociceptive and anti-inflammatory effects in a mouse model of arthritic knee pain. There were no obvious side effects on the liver, kidneys, or heart.